Algebraic Thinking Ability Test (ATAT) measuring 7th grade students using Rasch Measurement Model - Ibrahim, Hasniza; Khalid, Madihah; Abu Kassim, Noor Lide; Isa, Norshahira (UPSI Press, 2023)
Algebraic ability is crucial for students to master; however, studies have shown that many students struggle with learning algebra. In the Malaysian context, there is a lack of specific instruments to measure the algebraic ability of 13-year-old or 7th grade students. This study aims to develop a valid and reliable instrument to measure the algebraic thinking ability of 7th grade students in Malaysia. The Algebraic Thinking Ability Test (ATAT) assessment utilized the Winsteps Rasch Measurement Model. Fifteen main question items were selected, each further divided into subsections and treated as individual items, resulting in a total of twenty-seven items. These items were adapted and modified from the Form One or 7th grade Mathematics Textbook and TIMSS Mathematics questions. Each item had a different rating scale; thus, the Partial Credit Model (Group 0) was applied for analysis. The newly developed instrument was administered to 93 students from government schools in Selangor, Malaysia. The results indicated that the Algebra Test adequately described students' ability in algebra; however, the students' ability was found to be exceptionally low in this study. In other words, the respondents demonstrated lower capability as a group than the item difficulty. Overall, this research contributes to the development of a reliable and valid instrument to measure the algebraic ability of 7th grade students in Malaysia. The findings highlight the need for targeted interventions and support to improve students' algebraic thinking skills in the Malaysian education system.